Psychiatric Morbidity among Geriatric Patients Attending Psychiatric OPD of a Tertiary Care Hospital (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: The global elderly population is rapidly increasing, with Bangladesh's elderly demographic expected to rise significantly.Objective: This study explored pattern of psychiatric disorders and associated sociodemographic factors among elderly patients in a psychiatric hospital OPD setting, aiming to inform targeted management strategies.Methodology: This cross-sectional descriptive study was conducted at the National Institute of Mental Health's geriatric outpatient clinic in Dhaka, Bangladesh, from February to April 2024. A sample of 260 elderly patients aged 60 and above was selected using simple random sampling. Data collection involved a semi-structured questionnaire, the Mini International Neuropsychiatric Interview (M.I.N.I) for diagnosing psychiatric disorders, and the Bangla Mini-Mental State Examination (MMSE) for assessing cognitive function.Results: Sleep problems (25.8%) and low mood (20.4%) were the most frequent complaints, followed by elevated mood (17.3%), and anxiety, worry, or apprehension (16.2%). Among the patients 94.6% had one or more psychiatric disorders. The most common psychiatric disorders were schizophrenia spectrum disorders (28.8%) and major depressive disorder (25.8%). Significant associations were found between psychiatric disorders and age, occupation, family type, and physical illness.Conclusions: The study reveals a high prevalence of psychiatric disorders among elderly patients, highlighting the need for targeted mental health interventions.Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):41-46